2017
DOI: 10.1038/emi.2017.3
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity and transmission of a swine influenza A(H6N6) virus

Abstract: Subtype H6 influenza A viruses (IAVs) are commonly detected in wild birds and domestic poultry and can infect humans. In 2010, a H6N6 virus emerged in southern China, and since then, it has caused sporadic infections among swine. We show that this virus binds to α2,6-linked and α2,3-linked sialic acids. Mutations at residues 222 (alanine to valine) and 228 (glycine to serine) of the virus hemagglutinin (HA) affected its receptor-binding properties. Experiments showed that the virus has limited transmissibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 53 publications
1
17
0
Order By: Relevance
“…The internal genes of the influenza A(H1N1) pdm09 virus, which is prevalent in swine worldwide, increases the replication efficiency of H6N6 IAV in the lower respiratory tract of ferrets but not its transmissibility between ferrets. Experiments have shown that the virus has limited transmissibility through direct contact or through inhalation of infectious aerosolised droplets [ 81 ]. The aims of the study conducted by Sun et al were to understand the impacts of mutations in HA of the endemic H6N6 virus on its receptor-binding properties and also to assess the transmission potential and potential risks posed by reassortants of H6N6 with the A(H1N1)pdm09 virus.…”
Section: H6nx Viruses In Mammalian Species and Zoonotic Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The internal genes of the influenza A(H1N1) pdm09 virus, which is prevalent in swine worldwide, increases the replication efficiency of H6N6 IAV in the lower respiratory tract of ferrets but not its transmissibility between ferrets. Experiments have shown that the virus has limited transmissibility through direct contact or through inhalation of infectious aerosolised droplets [ 81 ]. The aims of the study conducted by Sun et al were to understand the impacts of mutations in HA of the endemic H6N6 virus on its receptor-binding properties and also to assess the transmission potential and potential risks posed by reassortants of H6N6 with the A(H1N1)pdm09 virus.…”
Section: H6nx Viruses In Mammalian Species and Zoonotic Infectionmentioning
confidence: 99%
“…In 2010, a H6N6 virus emerged in southern China, and since then, has caused sporadic infections among swine, with the virus binding to both α2,6 (human-like) and α2,3 (avian-like) sialic acids [ 81 ].…”
Section: H6nx Viruses In Mammalian Species and Zoonotic Infectionmentioning
confidence: 99%
“…For example, four amino acid substitutions in the HA receptor binding sites and one in the polymerase complex protein basic polymerase 2 (PB2), enabled H5N1 avian IAV to transmit in ferrets through airborne droplets [16]. Mutations at HA residues 222 (alanine to valine) and 228 (glycine to serine) increased the receptor binding preference of H6N6 avian IAVs to SA2,6Gal [17]. In addition to glycan receptor binding preference, genetic constellation of RNP complex and adaptative mutations in RNP genes, including PB1, have been shown to affect the host and tissue tropisms of IAVs [1821].…”
Section: Introductionmentioning
confidence: 99%
“…Its ability to replicate well in mice without pre-adaptation was an early indication that these viruses could cause cross-species infection in mammals [13][14]. H6 subtypes have since been isolated from cases of respiratory illness in pigs [15][16] and dogs [17]. Serologic surveillance of humans revealed that veterinarians and agricultural workers exposed to H6 IAV-infected poultry could also become infected [18][19] and in May 2013 the first human infection with an avian influenza H6 subtype linked to respiratory illness was reported in Taiwan.…”
Section: Introductionmentioning
confidence: 99%